(untitled) (Research, Society and Development, 2024)
“The judicial protection of possession in the Brazilian legal system reveals itself as an adoption of the absolute normative model of possession protection, in contrast to most European national legal systems, and establishes an independent possessory procedural protection in relation to the right to property” is the hypothesis that is proposed by the present article and validated with the investigation developed with the following objectives: investigate the historical development of the possessory and petitory actions in Roman Law; examine the level of independence and binding between the possessory judgment and the petitory judgment in the national legal systems; and identify particularities of the legal treatment of possession in Brazilian law, as well as the limits of its protection. The methodology used was based on a review of different doctrinal and normative sources with an analytical approach and on the exegesis of the current norms. As results, it was possible to identify and systematize the rules related to the judicial protection of possession that demonstrate that Brazil adopts a more independent and "guarantee" system of possessory protection (normative model of absolute protection of possession), as well as defining some of the singularities of the legal treatment of possession in Brazilian Law. With this, a propositional thesis is presented regarding the functioning and limits of the system of judicial protection of possession in Brazilian Law.